Strategi Pemulihan UMKM di Kelurahan Lapadde, Kota Parepare Pasca Pandemi Covid-19 Sejak 2022-2025 - Yusuf, Syarifuddin; Parman, Parman; natasia, Dita; Andini, Andini (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
The COVID-19 pandemic has had a major impact on the sustainability of Micro, Small, and Medium Enterprises (MSMEs), including those in Lapadde Subdistrict, Parepare City. This study aims to identify the recovery strategies implemented by MSME actors during the 2022–2025 period, as well as the factors that support and hinder the recovery process. The research employed a descriptive qualitative method, with the study conducted in Lapadde Subdistrict on December 1, 2025. The sample consisted of five MSME actors selected through purposive sampling. Data were collected through interviews, observations, and documentation, and were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that MSME actors have implemented recovery strategies such as product diversification, utilization of digital media, and cost efficiency, supported by local government programs. The main obstacles include limited capital and low digital literacy. Overall, MSME recovery is progressing positively but still requires continuous assistance and more equitable access to information to ensure sustainability.